ANALISIS YURIDIS TERHADAP AKTA PPAT SEMENTARA YANG DI BATALKAN MELALUI PUTUSAN PENGADILAN NEGERI BANTUL (Studi Kasus Putusan Pengadilan No. 21/Pdt. G/2010 PN. Btl) - , SITTI HAWA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study on The Judicial Analysis of Temporary Officer of Land Deed Processes (PPAT) Canceled by Bantul State Court Adjudication (A Case Study of Adjudication Number 21/Pdt.G/2010 PN.Btl) aimed to find factors causing the canceled authentic deed and what was legal consequence of the authentic deed canceled by State Bantul Court Adjudication Number 21/Pdt.G/2010 PN.Btl, and what the liability canceled authentic deed of temporary officer of land deed processes (PPAT) by Bantul State Court Adjudication Number 21/Pdt.G/2010 PN.Btl This study is a judicial-empirical research, namely: a research prioritizing a field research to collect primary data, conducted directly in objects associated with researched objects. Initial steps of research were taken by considering secondary data, conducting a juridical-normative research. The juridicalnormative research was a research conducted by prioritizing literature study to collect secondary data, then continued by research of data in location or parties associated with research objects to obtain primary data. The results of research indicated that the authentic deed of temporary officer of land deed processes (PPAT) canceled by the Bantul State Court Adjudication Number 21/Pdt.G/2010 PN Btl, was caused by legal defect of the authentic deed made by the temporary officer of land deed processes (PPAT), factors causing the canceled authentic deed, because legal meeting had found change made by Defendant I in making the authentic deed. Legal consequence of the canceled official document: it was canceled for law as to make all provisions existing in the authentic deed invalid, also land buying as object of sales contract was omitted and retuning to original condition before making sales. Responsibility of the canceled authentic deed of temporary officer of land deed processes (PPAT) : ending after legal action occurring in legal action of act was invalid.